Effectiveness of STEM-Based Disaster Preparedness Learning Integrated with Project-Based Learning (PjBL) in Enhancing Students' Critical Thinking Skills and Environmental Literacy - Syiva Nisa Ul Fadilah; Norma Eralita (Department of Physics Education, Universitas Mataram, 2026)
This study aimed to examine the effectiveness of the Project-Based Learning (PjBL) model integrated with STEM-based disaster preparedness learning in improving students’ critical thinking skills and environmental literacy, as well as to investigate students’ responses to learning the topic of Earth’s Structure and Its Development. A quasi-experimental method with a nonequivalent control group design was employed. The sample consisted of 56 seventh-grade students from SMPN 1 Semarang, including 28 students in the experimental group (Class VIIIC), who received PjBL integrated with STEM-based disaster preparedness learning, and 28 students in the control group (Class VIIIB), who were taught using the Discovery Learning model. Critical thinking skills were assessed using essay tests based on the FRISCO framework, whereas environmental literacy and students’ responses were measured using questionnaires. Data were analyzed using the Shapiro–Wilk normality test, normalized gain (N-gain) analysis, paired-samples t-test, and descriptive statistics. The results showed that students in the experimental group achieved greater improvement in critical thinking skills than those in the control group, with N-gain scores of 0.64 and 0.37, respectively, both categorized as moderate. The paired-samples t-test revealed a statistically significant improvement following the intervention (p < 0.001). The experimental group also demonstrated higher environmental literacy across the dimensions of knowledge, cognitive skills, attitudes, and behavior. Furthermore, students responded positively to the learning activities, with a practicality score of 85.53%, categorized as very practical. These findings indicate that integrating Project-Based Learning with STEM-based disaster preparedness learning is effective in enhancing students’ critical thinking skills and environmental literacy on the topic of Earth’s Structure and Its Development.